PERAN KOMITMEN ORGANISASIONAL DALAM MEMEDIASI PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION DI BALI ROCHMAT JAYA - Putra, I Gede Yudika; Ardana, I Komang (E-Jurnal Manajemen; Vol 7 No 12 (2018)DO - 10.24843/EJMUNUD.2018.v07.i12.p07, 2018)
Turnover intention is one form of behavior withdrawal in the world of work, but it is also a right for every individual to determine his choice company. Turnover is a serious problem in the field of Human Resource Management related to high turnover of labor. This study aims to determine the role of organizational commitment in mediating the influence of work stress on turnover intention. This research was conducted at PT Bali Rochmat Jaya, the sample was determined using census method and got a sample of 40 employees. Data collection using questionnaires. The analysis technique used is factor analysis and path analysis to test the effect of work stress and organizational commitment to turnover intention. The results of the first work stress have a negative effect on organizational commitment. Both of them show work stress positively influence to turnover intention. The third shows organizational commitment negatively affecting turnover intention, and finally the hypothesis of organizational commitment mediates significantly the relationship between work stress on turnover intention.